Genotype Identification of Carcharhinus sorrah and Carcharhinus leucas in Riau Islands Province - Petra Sagita; Sania Effendi; Efriyeldi Efriyeldi (Jurnal Natur Indonesia, 2026)
Sharks are predatory animals that live around coral reefs. This fish has slow growth and breeding limitations. Currently, its existence is increasingly threatened by the large number of captures, both as catch targets and bycatch, resulting in a decrease in the shark population in the waters. This study was conducted from November 2024 to January 2025 in Tanjung Pinang, Riau Islands Province. The purpose of this study was to genotype-identify Carcharhinus sorrah and Carcharhinus leucas, as well as to assess their conservation status. This study used a survey method. The analysis begins with several stages, namely extraction, amplification, electrophoresis, and sequencing. After identifying the species and its name, the next step is to determine its conservation status and international trade status. To find out the conservation status through the IUCN Red List and the international trade status through CITES Appendices. On the IUCN Red List, Carcharhinus sorrah is categorized as near threatened (NT), and Carcharhinus leucas is categorized as vulnerable (VU). Both species are listed in Appendix II of CITES